Park-people interaction - Its impact on livelihood and adaptive measures: A case study of Shivapur VDC, Bardiya District, Nepal - Paudyal, Narayan Prasad (Geographical Journal of Nepal, 2017)
This paper deals with the concept of theoretical and conceptual framework in a research with park-people interaction of Bardiya National Park (BNP) with specific reference to Shivapur Village Development Committee (VDC) of Bardiya district. The local people enter the park illegally and exploit the park resources like fodder, firewood, thatch, etc. They also try to kill wildlife either for food as traditional profession or for money. They frequently encounter with wildlife and get injured; sometimes they are killed. Similarly, wildlife cross the park boundary and destroy the crops and kill the livestock. Villagers also get their shelters and sheds damaged by them. BNP, therefore, has introduced various programmes to keep the conservation intact without disturbing the livelihood of Buffer Zone people. Several efforts, such as construction of Trench, Machan etc. have been made to address the issues associated with park people conflicts. In addition, endowment funds, such as Rahat Kosh, Apatkalin Kosh and Chetipurti Kosh have been established to provide and compensate to the human casualty and property (mainly building) damage.The Park-People interaction is the reality and the need is felt from both sides. Despite ups (harmony) and downs (conflicts) and despite differential use of resources by localities, the interface continues and is likely to continue so long as both these entities exist there. The need is to realize each-others limitations and strengthen their mutual understanding and the benefits. The Geographical Journal of Nepal Vol. 10: 167-180, 2017